Buzzing Communities: How to build bigger, better, and more active onli ne communities - Millington, Richard (Feverbee, 2012)
How to Build Bigger, Better, and More Active Online CommunitiesBuzzing Communities cuts through the fluff to offer a clear process for creat ing thriving online communities. This book combines a century of prove n science, dozens of real-life examples, practical tips, and trusted c ommunity-building methods. This step-by-step guide includes a lifecycl e for tracking your progress and a framework for managing your organiz ation's community efforts. This Book Will Help You to Understand what the members of your community really want. Dramatically increase the n umber of newcomers that become regulars. Avoid the mistakes most organ izations make when they try to build online communities. Develop a fan tastic, user-friendly website for your members. Grow your online commu nity to critical mass and beyond Keep members engaged and active in yo ur community. Measure the community's return on investment and explain the benefits to your organization.